The "timeless" use of influenza-like illness criteria for influenza detection in the tropics - Aung, Aung H. (2022)
Objective: We assessed the performance of influenza-like illness (ILI) case definitions by the Centers for Disease Control and Prevention (CDC), European Centers for Disease Control and Prevention and World Health Organization (WHO) in the tropics where seasonal patterns of respiratory viruses in acute upper respiratory tract infections (AURTIs) are ill-defined.